Penerapan Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Atas Undang-Undang Nomor I Tahun 1974 Tentang Perkawinan Terhadap Dispensasi Kawin di Pengadilan Agama Tuban - Muhari Muhari (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This research aims to describe the application of law number 16 of 2019 concerning amendments to law number i of 1974 concerning marriage regarding marriage dispensations in the Tuban religious courts. This research is qualitative research with a type of field research. Data collection techniques use interviews, observation and documentation. Analysis uses data reduction. data display and drawing conclusions. checking is done by data triangulation. The results of this research are that the Tuban religious court has implemented law number 16 of 2019 after the law was passed. With steps to provide outreach to the government concerned and the community. However, requests for marriage dispensation increased to 57% after the enactment of Law No. 16 of 2019, therefore it can be said that the implementation of Law No. 16 of 2019 is still not effective.